دور الاتصال للوكالة الوطنية لتسيير القرض المصغر لدعم الحرفيين بالاغواط - مسعودة جنيدي; د/ عبدالقادر بن جدو (جامعة عمار ثليجي الاغواط, 2024)
ملخص الدراسة باللغة العربية هدفت الدراسة إلى : 1) إبراز الدور الإتصالي للوكالة الوطنية لتسير القرض المصغر لدعم الحرفيين بالأغواط. 2) محاولة معرفة فعالية الدور الاتصاليللوكالة الوطنية لتسير القرض المصغر لدعم الحرفيين بالأغواط. 3) محاولة معرفة عملية التقييم لتسيير القرض المصغر لدعم الحرفيين. و تندرج دراستنا ضمن الدراسات أو البحوث الوصفية، وتم الإعتماد على المنهج الوصفي التحليلي، ونظرا لكبر مجتمع دراستنا، تم إختيار عينة قصدية طبقية، تمثلت في 50 حرفي وحرفية، أما أداة الدراسة فتمثلت في المقابلة والإستبيان. والنتائج المتوصل إليها في هذا البحثهي كالآتي: 1. الدور الاتصالي الذي تقوم به للوكالة الوطنية لتسير القرض المصغر لدعم الحرفيين بالأغواط، له فعالية كبيرة بحيث أن الوكالة توفر وسائل تواصل بالحرفيين، من خلال:تتواصل معهم إدارة الوكالة عن طريق الهاتف، و أيضا تتواصل معهم إدارة الوكالة عن طريق البريد الإكتروني، ووسائل أخرى، من بينها ( لقاءات، إجتماعات، الذهاب إلى مكان عملهم). 2. متابعة وكالة الوطنية لتسيير القرض المصغر لدعم الحرفيين تسهل لهم مشاريعهم بالأغواط، حيث أن الوكالة وضعت جميع الإمكانيات ووفرت مختلف الوسائل، من بينها: أنها وضعت في متناولنا كل الإمكانيات البشرية و المادية لا سيما وسائل التنقل للبلديات والمناطق البعيدة ، لتغطية كافة الإحتياجات وتمويل كافة الراغبين في إنشاء مشاريعهم ومرافقتهم وهذا هو هدف وغاية الوكالة، و القاعدة الأساسية للوكالة هي مرافقة ودعم من تمويلهم أو من كان تمويلهم ذاتي في البداية ويرغبون في توسيع من مشاريعهم ، فالوكالة سخرت كافة إمكانيتها المادية لدعم هؤلاء ، بهدف تحسين وتطوير التنمية المحلية من خلال دعم أكبر عدد من المؤسسات بإمكانها خلق مناصب عمل و تغطية إحتياجات المستهلك . 3. عملية التقييم لتسيير القرض المصغر لدعم الحرفيين تسهل لهم مشاريعهم بالأغواط، بحيث أن الوكالة تسعى لتسهيل عملية التمويل والإستفادة من القرض في أقل وقت ممكن، وتوفر الحملات الإعلانية التي نقوم بها على مستوى مراكز التكوين المهني والتي من خلالها تستقطب وتستهدف الحرفيين والمهنيين في إنشاء المشاريع ومرافقتهم من بداية المشروع إلى غاية نجاحه. 4. هناك بعض المشاكل التي تواجهها الوكالة مع الحرفيين وأصحاب المشاريع ونذكر منها مايلي :تلاعبات بعض ممن تم تمويل مشاريع في الأنشطة المخصصة لهم ، في حين يلجئون لبيع عتادهم الممول من طرفنا وهذا النوع من التحايل واجهناه كذا مرات، تغيير مقر الحرفيين كل مرة دون إبلاغنا وهذا ما يصعب علينا مرافقتهم ومتابعتهم ، تهربالمستفيدين من التمويل والقرض من تسديدها. الكلمات المفتاحية: الدور، الاتصال، الوكالة الوطنية لتسيير القرض المصغر، الحرفيين. Summary of the study in English The studyaimedto: 1) Highlighting the communication role of the National Agency for Microcredit Management to support artisans in Laghouat. 2) Trying to know the effectiveness of the communication role of the National Agency for Microcredit Management to support artisans in Laghouat. 3) Trying to know the evaluationprocess for administering a micro-loan to support artisans. Our studyfallswithin the framework of descriptive studies or research, and the descriptive analyticalmethodwasreliedupon. Given the large population of ourstudy, a stratifiedpurposivesamplewaschosen, consisting of 50 male and femalecraftsmen, while the studytoolwas the interview and questionnaire. The resultsreached in thisresearch are as follows: 1. The communication roleplayed by the National Agency for the Management of Microcredit to support artisans in Laghouat isvery effective, as the agencyprovidesmeans of communication with the artisans, through: the agency’s management communicateswiththem by phone, and the agency’s management alsocommunicateswiththem via e-mail, and othermeansOthers, including (meetings, meetings, going to theirworkplace). 2. Follow-up by the National Agency for Microcredit Management to support artisans and facilitatetheirprojects in Laghouat, as the agency has put in place all the capabilities and providedvariousmeans, amongthem: It has placed at ourdisposal all human and materialcapabilities, especiallymeans of transportation to municipalities and remote areas, to cover all needs and finance all Thosewhowish to establishtheirprojects and accompanythem, and thisis the goal and purpose of the agency, and the basic rule of the agencyis to accompany and support thosewho finance them or thosewhowere self-financed in the beginning and want to expandtheirprojects. The agency has harnessed all itsfinancialcapabilities to support these people, with the aim of improving and developing local developmentthroughgreater support. A number of institutions cancreate jobs and cover consumer needs. 3. The evaluationprocess for administering a micro-loan to support artisans facilitatestheirprojects in Laghouat, as the agencyseeks to facilitate the financingprocess and benefitfrom the loan in the shortest possible time, and providesadvertisingcampaignsthatwe carry out at the level of vocational training centersthroughwhichitattracts and targets artisans and professionals in establishingprojects. Accompanyingthemfrom the beginning of the projectuntilitssuccess. 4. There are someproblemsthat the agency faces withcraftsmen and projectowners, including the following: manipulations by some of thosewhoseprojectswerefunded in the activitiesassigned to them, whiletheyresort to sellingtheirequipmentfunded by us. We have encounteredthis type of fraudmany times, changing the headquarters of the craftsmenevery time withoutinforming us. This iswhatmakesitdifficult for us to accompany and followthem, as the beneficiaries of the financing and loansevaderepayment. Keywords:role, communication, National Agency for Microcredit Management, artisans.
دراسة ميدانية على عينة من الحرفيين بمدينة الاغواط